RANCANG BANGUN APLIKASI E-POIN UNTUK PENCATATAN DATA PELANGGARAN DAN PRESTASI AKADEMIK SISWA PADA SMK NEGERI 10 SURABAYA - Kusuma, Denny; Sagirani, Tri; Churniawan, Agus Dwi (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2018)
Abstract: SMK Negeri 10 Surabaya is a vocational high school located in the city of Surabaya. Problems that occur at SMK Negeri 10 Surabaya currently experiencing problems in terms of recording data violations and academic achievements that are still processed manually using a ledger. Teachers counseling difficulty to recapture the data of students who have violated and achievement data ever achieved by students / students.Based on the problems encountered, then one solution to overcome that is by making E- point application for recording data violation and data of student achievement of SMK Negeri 10 Surabaya.[0] The results of the process can be made into reports that can be used as information violations and achievements made by students / SMK Negeri 10 Surabaya.With E-points Application Development Design for Recording of Data on Student's Academic Abuse and Achievement At SMKN 10 Surabaya can facilitate Counseling Guidance teacher in processing data violation and academic achievement. Reports generated from this application are comparative reports of violations with student achievement and Reports of individual violations containing details of violations committed by students of SMK Negeri 10 Surabaya.Â Keywords: violation, achievement, counseling guidance